The Influence of school libraries on overall performance in Kenya Certificate of Secondary Education (KCSE) in day secondary schools in Municipality Ward, Meru County - Mutethia, Paul; Thuranira, Simon; Mwendwa , Mildred (African Journal of Science, Technology and Social Sciences, 2025)
This study investigates the influence of school libraries on overall performance in the Kenya Certificate of Secondary Education (KCSE) in day secondary schools within Municipality Ward, Meru County. The research addresses a critical gap in understanding the impact of library resources and utilization on academic success in this context. With a focus on four day secondary schools: Kinoru Secondary School, Meru Muslim Day Secondary School, CCM Township Day Secondary School, and Mwithumwiru Day Secondary School. This study will be guided by resource based learning theory and constructivism learning theory. The Resource-Based Learning Theory emphasizes that access to diverse educational materials enhances learning, while Constructivist Learning Theory highlights active, self-directed, and collaborative knowledge construction. Together, these theories suggest that well-equipped and effectively utilized school libraries significantly improve students’ KCSE performance. The study employs qualitative methods, including interviews and observations, to gather data from head teachers and teachers in charge of libraries who are informants in this study. In this study the sample population will be 8 respondents, out of which 4 will be the headmasters of those day secondary schools and the other 4 will be the teachers who are in charge of the schools libraries. The findings reveal a significant positive correlation between the availability and adequacy of library resources and students’ KCSE performance. Pearson’s correlation coefficient quantify the relationship between library resources and KCSE performance, with a strong positive r value of 0.75 indicating that better-equipped school libraries significantly enhance students’ KCSE scores in day secondary schools in Municipality Ward, Meru County. Effective measures, such as extended library hours and collaborative teaching strategies, enhance the accessibility and relevance of library resources. Regular collaboration between teachers and teachers in charge of libraries is pivotal in integrating library activities with the curriculum, thereby supporting students’ academic endeavors. Despite challenges like insufficient funding and limited resources, schools employ various strategies to overcome these barriers, including seeking external funding, updating collections, and forming community partnerships. Monitoring and evaluation practices indicate a positive correlation between regular library usage and higher KCSE performance. The study underscores the importance of continued investment in library resources, infrastructure, and collaborative efforts to further strengthen the impact of school libraries on academic success in day secondary schools in Municipality Ward, Meru County Key words: school libraries; performance